Contribution to the knowledge of the ptyctimous mite genus Austrophthiracarus (Acari, Oribatida, Steganacaridae) with descriptions of two new species from China - Liu, Dong (Zootaxa, 2020)
Two new species of oribatid mite family Steganacaridae, Austrophthiracarus paralongisetosus sp. nov. collected from Sichuan Province, and Austrophthiracarus bacilliformis sp. nov. collected from Heilongjiang Province, are described and illustrated. A key to all known Chinese species of Austrophthiracarus is proposed to facilitate further identification of this group.